The influence of periodontal status and serum biomarkers on salivary leptin levels in systemic lupus erythematosus patients - Leslie A. da Silva; Consuelo P.C. Marques; Izabel C.V. de Oliveira; Mayra M. Franco; Vandilson P. Rodrigues; Bruno B. Benatti (Saudi Dental Journal)
Objective: This study aimed to investigate the influence of periodontal status, clinical data, and serum markers on salivary leptin levels in patients with systemic lupus erythematosus (SLE). Methods: A case–control study was conducted with 38 patients with SLE and 29 healthy controls. Periodontal data included periodontal probing depth (PPD), clinical attachment level (CAL), and gingival bleeding on probing (BOP). Stimulated saliva samples were collected to analyze salivary leptin levels. Clinical and serum data were collected from the SLE group. Statistical analysis included the t-test, Mann–Whitney test, Spearman correlation coefficient, and a structural equation model. Results: The SLE group had a lower salivary leptin level than the control group (P = 0.002). The model revealed that SLE had an inverse and independent effect on salivary leptin (standardized estimate =  − 0.289, P = 0.023). Moreover, salivary leptin level negatively correlated with the serum levels of triglyceride, creatinine, and leukocytes, positively correlated with the serum total cholesterol, but was not significantly correlated with the periodontal status. Conclusion: These findings suggest that patients with SLE have a lower salivary leptin level. In addition, the level of salivary leptin does not appear to be related to periodontal status in patients with SLE.